2022
DOI: 10.1111/tgis.12939
|View full text |Cite
|
Sign up to set email alerts
|

Explainable spatiotemporal reasoning for geospatial intelligence applications

Abstract: This article explores the design, implementation, and querying of a prototype system for automated spatial reasoning for geospatial intelligence applications, called NEXUS.The system combines multiple different reasoning components that can support a wide range of spatiotemporal queries. Fundamental to the requirements of intelligence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Chan et al [39] showed that object motion could be recognized from low-level video information by mapping vocabulary and object motion using an ontology mapping technique. Duckham et al [40] designed and implemented a prototype of an automated spatial reasoning system for geospatial information applications called NEXUS and showed that it could perform a variety of spatio-temporal queries and also explain why it reached the conclusions it did.…”
Section: Related Ontologies and Studiesmentioning
confidence: 99%
“…Chan et al [39] showed that object motion could be recognized from low-level video information by mapping vocabulary and object motion using an ontology mapping technique. Duckham et al [40] designed and implemented a prototype of an automated spatial reasoning system for geospatial information applications called NEXUS and showed that it could perform a variety of spatio-temporal queries and also explain why it reached the conclusions it did.…”
Section: Related Ontologies and Studiesmentioning
confidence: 99%